Quark mass dependence of the low-lying charmed mesons at one loop in HHχPT - Fernando Gil-Domínguez; Raquel Molina (Physics Letters B, 2023)
We study the light and heavy quark mass dependence of the low-lying charmed mesons in the framework of one-loop HHχPT. The low energy constants are determined by analyzing the available lattice data from different LQCD simulations. Model selection tools are implemented to determine the relevant parameters as required by data with a higher precision. Discretization and other effects due to the charm quark mass setting are discussed.